Atom Transfer Radical Polymerization of Pyrrole-Bearing Methacrylate for Production of Carbonyl Iron Particles with Conducting Shell for Enhanced Electromagnetic Shielding - Mrlík, Miroslav; Kollár, Jozef; Borská, Katarína; Ilčíková, Markéta; Gorgol, Danila; Osicka, Josef; Sedlačík, Michal; Ronzová, Alena; Kasák, Peter; Mosnáček, Jaroslav (International journal of molecular sciences, 2022)
The conducting polymer poly(2-(1H-pyrrole-1-yl)ethyl methacrylate (PPEMA) was synthesized by conventional atom transfer radical polymerization for the first time from free as well as surface-bonded alkyl bromide initiator. When grafted from the surface of carbonyl iron (CI) a substantial conducting shell on the magnetic core was obtained. Synthesis of the monomer as well as its polymer was confirmed using proton spectrum nuclear magnetic resonance (1H NMR). Polymers with various molar masses and low dispersity showed the variability of this approach, providing a system with a tailorable structure and brush-like morphology. Successful grafting from the CI surface was elucidate by transmission electron microscopy and Fourier-transform infrared spectroscopy. Very importantly, thanks to the targeted nanometer-scale shell thickness of the PPEMA coating, the magnetization properties of the particles were negligibly affected, as confirmed using vibration sample magnetometry. Smart elastomers (SE) consisting of bare CI or CI grafted with PPEMA chains (CI-PPEMA) and silicone elastomer were prepared and dynamic mechanical properties as well as interference shielding ones were investigated. It was found that short polymer chains grafted to the CI particles exhibited the plasticizing effect, which might be interesting from the magnetorheological point of view, and more interestingly, in comparison to the neat CI-based sample, it provided enhanced electromagnetic shielding of nearly 30 dB in thickness of 500 μm. Thus, SE containing the newly synthesized CI-PPEMA hybrid particles also exhibited considerably enhanced damping factor and proper mechanical performance, which make the material highly promising from various practical application points of view.
Keywords: povrchové vlastnosti; Pyrroles; magnetic particle; polymerizace; polymer brushes; elektromagnetické jevy; železo; atom transfer radical polymerization; methakryláty; pyrroly; Electromagnetic Phenomena; Polymers; interference shielding; polymery; Iron; Polymerization; Surface Properties; Methacrylates; smart elastomer